3x-(5-6+7)=8-4x

Simple and best practice solution for 3x-(5-6+7)=8-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(5-6+7)=8-4x equation:


Simplifying
3x + -1(5 + -6 + 7) = 8 + -4x

Combine like terms: 5 + -6 = -1
3x + -1(-1 + 7) = 8 + -4x

Combine like terms: -1 + 7 = 6
3x + -1(6) = 8 + -4x

Multiply -1 * 6
3x + -6 = 8 + -4x

Reorder the terms:
-6 + 3x = 8 + -4x

Solving
-6 + 3x = 8 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-6 + 3x + 4x = 8 + -4x + 4x

Combine like terms: 3x + 4x = 7x
-6 + 7x = 8 + -4x + 4x

Combine like terms: -4x + 4x = 0
-6 + 7x = 8 + 0
-6 + 7x = 8

Add '6' to each side of the equation.
-6 + 6 + 7x = 8 + 6

Combine like terms: -6 + 6 = 0
0 + 7x = 8 + 6
7x = 8 + 6

Combine like terms: 8 + 6 = 14
7x = 14

Divide each side by '7'.
x = 2

Simplifying
x = 2

See similar equations:

| 3a+b+a= | | 2.5x-6.2=3.7x-5.8 | | 8(x+1)+3(2x-2)=44 | | 3x+4x+8-2=6x-14+2 | | 1.4t+2.1=0.9t | | -5(2x+1)=35 | | 5-0.5(x-6)=4 | | 8x+5=6x-3 | | 11-8(7-6x)=5(7-x)-11x | | 2-3x+7=22 | | x+x+x=9 | | 8(x-2)=4(2x+3) | | 4(x+2)=3(1.5+x) | | 5a^2+18a+9=0 | | 10-2x=3x+4 | | 3x^2=10x+2 | | X-4=96 | | y=-0.5(50)+105 | | y=-0.5(40)+105 | | y=-0.5(30)+105 | | x+97=91 | | y=-0.5(20)+105 | | x+x+12=58 | | n^2=5n-63 | | -1(x-18)+3(x+12)=6x+24 | | 4(3x-5)=6(2x+3) | | -29+47-15+6= | | 4y-6(y-5)=2 | | 7-(6x+5-3)+2x= | | 0.6(4x+8)=1.1-(x+2) | | -4(x-3)=2(3x+6) | | 3.2x-2(x-1.6)=28.46 |

Equations solver categories